Imogolite in Water: Simulating the Effects of Nanotube Curvature on Structure and Dynamics - Baltazar-Rojas, S; Allende-Prieto, S; Rojas-Núñez, J (Elsevier Ltd, 2020)
Imogolite is a fascinating inorganic nanotube that is found in nature or synthesized in a laboratory. The synthesis process is carried out in liquid media, and leads to the formation of almost monodisperse diameter nanotubes. Here we investigate, employing classical molecular dynamics simulations, the interaction of water and imogolite for nanotubes of several radii. We established that water penetrates the pores of N = 9 and larger nanotubes, and adopts a coaxial arrangement in it. Also, while water molecules can diffuse along the center of the nanotube, the molecules next to the inner imogolite walls have very low mobility. At the outer nanotube wall, an increase of water density is observed, this effect extends up to 1 nm, beyond which water properties are bulk-like. Both phenomena are affected by the imogolite curvature. © 2020 Elsevier B.V.